Usability of semiautomatic segmentation algorithms for tumor volume determination - Mahr, Andreas; Levegrün, Sabine; Bahner, Malte Leonardo; Kreß, Jürgen; Schlegel, Wolfgang (Investigative radiology, 1999)
Rationale and objectives: Tumor volume is an important parameter for clinical decision making. At present, semiautomatic image segmentation is not a standard for tumor volumetry. The aim of this work was to investigate the usability of semiautomatic algorithms for tumor volume determination. Methods: Semiautomatic region- and volume-growing, isocontour, snakes, hierarchical, and histogram-based segmentation algorithms were tested for accuracy, contour variability, and time performance. The test were performed on a newly developed organic phantom for the simulation of a human liver and liver metastases. The real tumor volumes were measured by water displacement. These measured volumes were used as the gold standard for determining the accuracy of the algorithms. Results: Variability of the segmented volumes ranging from 3.9 ± 3.2% (isocontour algorithm) to 11.5 ± 13.9% (hierarchical segmentation) was observed. The segmentation time per slice varied between 32 (volume-growing) and 72 seconds (snakes) on an IBM/RS6000 workstation. Conclusions: Only the region-growing and isocontour algorithms have the potential to be used for tumor volumetry. However, further improvements of these algorithms are necessary before they can be placed into clinical use.